Impact Of Educational Package On Knowledge Regarding Childbirth Among Primigravida Mothers - Sharma, Meenakshi; kumar, Periadurachi (Journal of Neonatal Surgery, 2025)
Background: Primigravida mums do not understand childbirth well, which might affect their self-assurance and readiness for the process. The purpose of this research was to determine whether or not a prenatal education program was successful in increasing first-time mums' understanding of how to be physically and mentally ready for a delivery. Objectives: The research's purpose was to compare participants' knowledge scores before and after receiving an educational package and assess the package's effectiveness. Methods: Forty first-time mums who sought medical attention at a clinic participated in the study using a pre-experimental, one-group pre-test-post-test design. There was a systematic knowledge questionnaire given both before and after the training package that included labour phases, pain management, and skills for preparing for delivery was delivered. “A paired t-test and descriptive statistics (such as percentages, means, and standard deviations) were used to analyze the data”. Results: The post-test knowledge score was 24.73 (SD = 5.970), a significant increase from the mean pre-test score of 17.28 (SD = 6.477) (t = -7.235, p =.000). Forty percent of the participants were between the ages of 23 and 27, 37.5% had completed some level of formal education, and 57.5% were familiar with the process of giving birth naturally. Conclusion: Primigravida mothers were better prepared for a delivery after receiving the instructional package, which showed a significant increase in knowledge levels. These results lend credence to the idea that prenatal care should include organized educational treatments to better prepare mothers. However, they also call for further research with bigger samples and control groups to draw firm conclusions